Sovereign Natural Disaster Insurance For Developing Countries : A Paradigm Shift In Catastrophe Risk Financing - Ghesquiere, Francis (The World Bank, 2007)
Economic theory suggests that countries should ignore uncertainty for public investment and behave as if indifferent to risk because they can pool risks to a much greater extent than private investors can. This paper discusses the general economic theory in the case of developing countries. The analysis identifies several cases where the government's risk-neutral assumption does not hold, thus making rational the use of ex ante risk financing instruments, including sovereign insurance. The paper discusses the optimal level of sovereign insurance. It argues that, because sovereign insurance is usually more expensive than post-disaster financing, it should mainly cover immediate needs, while long-term expenditures should be financed through post-disaster financing (including ex post borrowing and tax increases). In other words, sovereign insurance should not aim at financing the long-term resource gap, but only the short-term liquidity need